Environmental measurements from the Ebro Delta coastal area during MERS-BLUEISLAND cruise (November 2019) - Addante, Marina; Grelaud, Michaël; Langer, Gerald; Maiorano, Patrizia; Bonomo, Sergio; Álvarez, Marta; Johnson, Roberta; Ziveri, Patrizia (PANGAEA, 2024)
The present dataset contains environmental variables: temperature, salinity, fluorescence, turbidity, nitrite, nitrate, phosphate, silicon dioxide, total alkalinity, dissolved inorganic carbon and pH. The samples were collected between Barcelona and the Ebro Delta (Western Mediterranean), during the MERS-BLUEISLAND cruise in November 2019, with rosette Niskin bottles equipped with CTD investigating the photic zone (0-200 m).
Keywords: Ebro River Delta; Environmental variables